Retrospective analysis of gastrointestinal bleedings with direct oral anticoagulants reported to EudraVigilance - Moudallel, Souad; van den Eynde, Celien; Malý, Josef; Rydant, Silas; Steurbaut, Stephane (Naunyn-Schmiedeberg's archives of pharmacology, 2023)
Direct oral anticoagulants (DOACs) are increasingly used and are an important cornerstone in antithrombotic therapy. Adverse drug reactions (ADRs) such as bleedings have only partially been investigated during clinical trials. The primary goal was to analyse pharmacovigilance data based on spontaneous reports of gastrointestinal (GI) bleedings with DOACs reported to EudraVigilance. A second goal was to compare GI safety profiles between DOACs based on these signals. All DOAC related GI bleedings mentioned in individual case safety reports (ICSRs) from 2012 till 2017 in the European Economic Area were classified in four GI categories based on the reported site of occurrence of the haemorrhage. Age group and gender of the patient, seriousness and ADR outcome, and the reporter's qualification were assessed per category and per DOAC. Disproportionality analyses were performed to evaluate whether or not the reported ADRs were more prevalent with a given DOAC. ICSRs were bleeding-related in about half of the cases (n = 28,992/53,471). Of these bleedings, >25% was GI-related. Most patients experiencing GI bleedings were between 65 and 85 years old, with no obvious differences between men and women. Stomach, ulcer-related duodenal, and rectal bleedings were the most reported GI bleedings with a fatal outcome in 5.8%, 7.5%, and 9.8% of the cases for rivaroxaban, apixaban, and dabigatran, respectively. The disproportionality data suggest that dabigatran is more frequently involved in GI bleeding events than the other DOACs. DOACs were significantly associated with GI bleedings. Although the data should be interpreted with caution, it seems that dabigatran was associated more often than other DOACs with GI bleedings based on the analysis of spontaneous pharmacovigilance reports.
Keywords: Direct oral anticoagulants (DOACs); Humans; dabigatran; Dabigatran; Stroke; Female; Aged; Gastrointestinal bleedings; Pharmacovigilance; senioři; lidé; Administration, Oral; Atrial Fibrillation; Adverse drug reactions (ADRs); rivaroxaban; cévní mozková příhoda; ženské pohlaví; Male; gastrointestinální krvácení; Retrospective Studies; Gastrointestinal Hemorrhage; Aged, 80 and over; senioři nad 80 let; retrospektivní studie; aplikace orální; Rivaroxaban; mužské pohlaví; antikoagulancia; EudraVigilance; Anticoagulants; fibrilace síní